Kearifan Menyikapi Liberalisasi Pendidikan - Jalal, Pambudi M. (Unisia, 2010)
The economy aspect will influence on education management. The education management should accomodate the market trends, and its trends toward profit taking. Thus, the changing of this orientationis afraid of some educators because this will ignore the main goal of education, namely to protect Indonesians and the whole of Indonesian archipelago, to develop the public welfare, to educate this nation, and to participate in realizing world order. If this happens, the indentity and the ideology of Indonesia can not be reached because of education liberalization. This will imply the ideology and morality destruction.